Chemical Composition of Beekeeping Products, Use in Medicine and Importance in National Economy - B.A. Qaxramonov; A.I. Amirov; M.I. Bosimova (Zien Journals, 2023)
This article provides information on the chemical composition of beekeeping products, their use in the field of medicine in the prevention and treatment of diseases, and their importance in the national economy.
Keywords: bacteriocide; pathogen; diphtheria; intestinal bacilli; streptococcus; staphylococcus